Ultrasensitive and low detection limit of acetone gas sensor based on ZnO/SnO2 thick films. Issue 59 (30th September 2020) - Chen, Yanping; Cao, Yue
Abstract : XRD patterns of ZnO/SnO2 powders. Abstract : In this study, we synthesized ZnO/SnO2 hybrid sensing nanostructures by a sol–gel method. The structures, composition and morphologies of the synthesized products were thoroughly studied by X-ray diffraction (XRD), field-emission electron scanning microscopy (FESEM) and transmission electron microscopy (TEM). After the gas sensing test, we found that the sensing performance of the ZnO/SnO2 composite is improved obviously compared with that of single components ZnO and SnO2 . The response to 0.5 ppm acetone reaches 3.36, almost twice that of pure ZnO and SnO2 . Meanwhile, the detection limit can be reduced to the ppb level. The enhanced acetone sensing performance was mainly attributed to the formation of n–n heterojunctions and the synergistic effect of ZnO and SnO2 .